Modeling and analysis of common Philippine-made concrete hollow block structures using rigid body-spring discrete element method - Tadiosa, Jerome Z.; Mangoba, John Dee A.
The 2013 Bohol tragedy caused by a magnitude 7.2 earthquake has proven the vulnerability of common Philippine concrete hollow block houses to strong ground motion. In this study, computer models of common Philippine-made CRE structures were used to assess their performance and seismic vulnerability and to introduce a method of determining sections/components which are highly likely to collapse and therefore providing a good basis to strengthen the structure. The study focuses on the derivation of the shear and normal stiffness of springs from the material properties of a CHB unit incorporating the grout and mortar fillings though volumetric transformation of the dimensions using material ratio. Springs were connected at the interfaces of neighboring CHB units at several contact points. In-plane loading was subjected on the wall models to determine the shear and flexural failure mechanisms. Simulation under the 1995 Kobe earthquake record was performed on a common four-walled structure. Behavior of failure and collapse was observed then validated using experimental results from literature. The method used for simulations was effective in showing failure patterns of models subjected to specific load cases although more numerical validation of results is recommended.